The COVID 19 pandemic in the management of restaurants in the Urubamba districtic 2020 - Castillo Mamani, Julio Asencio (2022)
ABSTRACT - SUMMARY The objective of this research was to establish to what extent does the framework of the COVID-19 pandemic influence the management of tourist restaurants in the Urubamba 2020 district, as well as how this health crisis influences profitability, employability and which ones have been the new strategies that have been adopted so that these businesses continue to operate during the economic reactivation? For this purpose, the research was based on a descriptive-correlative methodology with a quantitative approach, as well as a non-experimental design. The present research study had considerable limitations in terms of the research background related to the tourist restaurant category both nationally and internationally as a result of the COVID-19 pandemic. Likewise, the fear of contagion with the owners, collaborators and vice versa in face-to-face interviews in such a way, the information that was collected was scarce and whose discussion of the research work was relatively brief. KEY WORDS: COVID-19 pandemic, Restaurant management, health crisis.